Jamblang (Syzygium cumini) leaf extract decreased hydrogen peroxide in lead acetate-induced rats - Rauza Sukma Rita; Elmatris Sy; Endrinaldi (Acta Biochimica Indonesiana, 2022)
Background: Free radicals are atoms or molecules with one or more unpaired electrons. Lead acetate has been reported to increase the presence of free radicals in the body. Objective: This study aims to investigate the effect of oral administration of jamblang (Syzygium cumini) leaf extract on hydrogen peroxide (H2O2) serum levels in rats induced with lead acetate. Methods: A total of 24 male rats were divided into three groups: the negative control, the positive control, and the treatment group. The negative control group received a standard diet, the positive control group received lead acetate at a dose of 40 mg/kg body weight, and the treatment group received lead acetate at the same dose along with jamblang leaf extract at a dose of 150 mg/kg body weight. Lead acetate and jamblang leaf extract administration was carried out for 30 days. Afterward, serum H2O2 levels were examined using the colorimetry method. Results: Results revealed that H2O2 levels in the negative control, positive control, and treatment groups were 3.08±0.24, 4.94±0.75, and 3.44±0.65 nmol/L, respectively. Significant differences were observed between the groups, as well as between the negative control and positive control, and between the positive control and treatment group. Conclusion: The study showed that jamblang leaf extract can reduce hydrogen peroxide levels in Wistar rats treated with lead acetate, indicating its ability to address oxidative stress.